Мікропроцесорна система автокалібрування цифрових термоелектричних термометрів в умовах їх експлуатації - Скрипник, Ю.; Юрчик, Г. (Видавництво Національного університету «Львівська політехніка», 2003)
In the present work it’s being analyzed the method aimed to improve accuracy and provision of metrological reliability of the digital thermo-electric thermometers using their periodical self-verification in service conditions.